Sources of the terrigenous and volcanic ash material in the Middle Volgian deposits of the Eastern Russian Platform - K.I. Nikashin; S.O. Zorina (Учёные записки Казанского университета: Серия Естественные науки)
The current research aims to reconstruct sources of the rocks and pyroclastic input in the epeiric sea of the Eastern Russian Platform in the Latest Jurassic. Nine samples of the Volgian mudrocks, black shales, and sandstones from the Tatar Shatrashany borehole section and Gorodischi outcrop were investigated using the mineralogical, ICP-MS, XRD, electron microscopy, and Raman spectroscopy analyses. Accessory minerals of various mineral associations identified in sandstones indicate the input of terrigenous material from different sources. The Paleozoic deposits of the Volga-Ural and Voronezh Uplifts, igneous and metamorphic rocks of the Voronezh Crystalline Massive (including Pavlovsk granite complex), Ural Folding Region, and Baltic Shield were found to be the most likely sources. The morphology of zircons revealed their association with felsic alkaline rocks. Volcanic glasses and “camouflaged” pyroclastic material (heulandite, smectite, and mixed-layer mineral) were identified in mudrocks and black shales. The proportion of both smectite and mixed-layer mineral varies from 20% to 27% throughout the section, whereas the amount of heulandite reaches 25% in the Promzino black shales. The Raman spectroscopy analysis showed the intermediate-acid composition of volcanic glasses from the Promzino Formation. According to the results obtained in the study, volcanic arcs of the north margin of the Tethys and the High Arctic Large Igneous Province are the major sources of the pyroclastic material.